Dynamic Study of VSA and TSA Processes for VOCs Removal from Air - Rawnak Talmoudi; Amna AbdelJaoued; Mohamed Hachemi Chahbani (International Journal of Chemical Engineering)
Volatile organic compounds are air pollutants that necessitate to be eliminated for health and environment concerns. In the present paper, two VOCs, that is, dichloromethane and acetone are recovered by adsorption on activated carbon from a nitrogen gas stream. Experimental adsorption isotherms of the two VOCs are determined at three different temperatures 298, 313, and 323 K by the dynamic column breakthrough method. The dynamic mathematical model succeeds to predict satisfactorily the experimental breakthrough curves for pure VOCs and different binary mixtures for various conditions. Thus, the validated dynamic mathematical model has been used as a simulation tool for optimization purposes of VSA and TSA processes in order to achieve the highest performances under the given constraints. The effects of the adsorption step duration, the vacuum pressure, and the desorption temperature on the recovery of dichloromethane and acetone have been studied. A recovery of 100% of the two VOCs could be attained. However, the adsorption step duration should be determined precisely so as not to affect the recovery and alter the quality of air being purified due to the breakthrough of VOCs. The vacuum pressure and the desorption temperature should be carefully chosen in order to both reduce the energy consumption and shorten the purge step duration. Regeneration by hot nitrogen stream seems to be more efficient than regeneration by reducing pressure.